Neurosurgical Management of Intractable Temporal Lobe Epilepsy by Amygdalohippocampectomy Plus Anterior Temporal Lobectomy: Report of Initial Three Pediatric Cases with Short Literature Review - Chowdhury, FH; Haque, MR; Chowdhury, SMNK; Dey, AR; Sarker, AC; Islam, MS (Bangladesh Journal of Child Health, 2012)
Temporal Lobe Epilepsy (TLE) is one of the most common surgical epilepsy that is usually resistant to antiepileptic drugs and surgery is the treatment of choice. This type of epilepsy may be due to Mesial Temporal Sclerosis (MTS), tumors [i.e. low grade glioma, Arterio-Venous Malformation (AVM) etc],trauma, infection (Tuberculosis),parasitic infestation (e.g. Schistosomiasis) etc. Here we report three cases of surgically treated TLE in pediatric age that was due to MTS and low grade ganglioglioma. In all three cases the only presenting symptom was complex partial seizure (Psychomotor epilepsy) for which all underwent scalp electro-encephalography (EEG) and Magnetic Resonance Imaging (MRI) of Brain. All three patients were managed by amygdalohippocampectomy plus standard anterior lobectomy. In post operative period the cases were seizure and disease free till last follow up. We did not face any nominal dysphasia, memory disturbances, hemi paresis or visual field defect. DOI: http://dx.doi.org/10.3329/bjch.v35i1.10370 BJCH 2011; 35(1): 26-31